Regional hypertrophy, the inhomogeneous muscle growth: a systematic review - Zabaleta-Korta, A.; Fernández-Peña, E.; Santos-Concejero, J. (Strength and Conditioning Journal, 2020)
A literature search was performed in 2 databases (PubMed and Scopus) on May 22, 2019. From the 14 studies included in the review, 13 found that the anatomical cross-sectional area of some regions of a muscle increased to a greater degree than others. Some studies found increases in the distal region, others reported increases in the middle region, and some found differences between regions but did not report which increased the most. Hypertrophy between and within muscle heads is not homogeneous, confirming that regional hypertrophy actually happens in the quadriceps femoris, triceps brachii, and biceps brachii muscles.